Suberogorgin vs N-cyclohexyl suberogorgamide effects on urine, respiration, and blood pressure in rat and cat. - Du Wen-Duo; Xu Shi-Bo (Acta Pharmacologica Sinica; Vol 17, No 1 (January 1996): Acta Pharmacologica Sinica, 2016)
"AIM: To compare the pharmacological actions of suberogorgin (Sub) and N-cyclohexyl suberogorgamide (N-CS). METHODS: Urine was collected from rats and anesthetized cats which had been loaded with water. The concentrations of Na+ and K+ in urine were determined in ICAP-9000 atomic emission spectrometry. An equitoxic (1/50 LD50) dose of Sub and N-CS was used in cats. RESULTS: The cat urine was decreased by 63% after i.v. Sub 0.4 mg.kg-1, but increased by 25% after i.v. N-CS 1.5 mg.kg-1, lasting at least 9 h. Sub and N-CS increased the respiratory rate and tidal volume, but did not change the blood pressure. The rat urine was decreased by 48% after i.p. Sub 1.3 mg.kg-1, but increased by 14% after i.p. N-CS 3.2 mg.kg-1. Sub and N-CS increased the concentrations of Na+ and K+ in rat urine. These effects lasted at least 24 h. CONCLUSION: Sub is an antidiuretic, while N-CS is a diuretic drug. "